Controllable wetting and evaporation of a sessile colloidal droplet - Ren, Junheng (Nanyang Technological University, 2021)
The wetting and evaporation of the sessile colloidal droplet are receiving increasing attention due to their potential in controlling droplet drying behavior and acquiring desired dried patterns. It is closely related to the wetting manner of the sessile droplet which is dominated by the interplay effect of the liquid type and surface wetting property. Motivated by this, this study aims to investigate the wetting and evaporation dynamics of colloid droplets with a solution or suspension and to explore potential applications with the surfaces. The first and second efforts are to model nanofluid droplet drying on flat surfaces, under the pinning and depinning wetting conditions. A three-dimensional (3D) diffusion-limited cluster-cluster aggregation model has been developed to simulate the pattern formation of pinned drying droplets, with accounting for the enhanced Marangoni effect, the strong particle aggregation possibility, and the particle adsorption at the liquid-vapor interface. The formation of a disk pattern inside an outer ring has been simulated. In the case of the dewetting droplet drying, branched structures are observed to form. A 3D kinetic Monte Carlo model has been developed, including the particle diffusion and contact line retreating effect. The numerical model reproduced the particle deposits agreeable to the experimental ones. The third effort of this study is to experimentally investigate the evaporative dynamics and deposition patterns of sessile saline droplets on various flat surfaces or with surfactant additives. On the silicon wafer and poly (methyl methacrylate) (PMMA) substrate, the pure saline droplets undergo a unique period of drying where the contact angle keeps increasing and the contact line keeps receding. On the soda lime glass, the droplets always evaporate in a pinned mode. The lower wettability and the weaker pinning effect of silicon wafer and PMMA substrate result in the morphology of crystalline cubes at the droplet center. While the high wettability and strong pinning effect of soda lime glass lead to exterior cracked layers of salt and interior separated small cubes for low salt concentrations, whereas large crystalline chunks stay near the droplet rim for high salt concentrations. With the dilute surfactant additives in the saline solution, the droplet resting on the silicon wafer exhibits an initial autophobing effect with its wetting contact angle rising continuously in the later evaporation process. As the surfactant concentration increases, the initial autophobing effect is weakened and the droplet gets pinned gradually. Under a relatively high surfactant concentration, dendritic precipitation patterns are observed to form around the central crystals for high salt concentration and to cover the whole wetted area for the dilute salt concentration. The fourth section of the study is to explore the evaporation and wetting dynamics of sessile colloidal droplets on a micropyramid patterned surface. The droplet liquid property is controlled by adding potassium chloride or cetyltrimethylammonium bromide into the pure water. The saline droplet formed an initial octagonal wetting interface on the patterned surface and then experienced constant contact radius and constant contact angle evaporation mode before crystallization happened. The evolution of the wetting interface from octagonal to circular shape was found to be brought by the receding of the contact line. For the surfactant droplets, an “octagonal-to-square” wetting transition was found to exist during the evaporation process. The maintenance of droplet octagonal wetting shape could be attained at a dilute surfactant concentration and square shape at a high surfactant concentration. The above study on how a sessile droplet dries differently on smooth surfaces, patterned surfaces, and how it varies under different liquids has contributed to the further understanding of droplet wetting and drying behavior. Future recommendations call for experimental work of controllable particle depositions on the patterned surfaces and the related modeling on droplet wetting and drying dynamics.